Islam Raḥmatan Li-l-‘Ālamīn and Civil Tolerance in Indonesia: The Legacy of Ahmad Hasyim Muzadi - Nasih, Ahmad Munjin; Taufiqurrahman, Febri; Hidayatullah, Muhammad Fahmi; Yani, Muhammad Turhan (Teosofi: Jurnal Tasawuf dan Pemikiran Islam, 2024)
This study aims to highlight the significance of Ahmad Hasyim Muzadi’s thoughts on civil tolerance, arguing that his paradigm can be used in conflict resolution. It explores the significance of Muzadi’s ideas in the context of Indonesia’s religious diversity, employing a qualitative approach through textual analysis. The findings revealed that Muzadi pioneered the concept of civil tolerance—a nuanced, humanized type of religious coexistence and mutual respect that goes beyond surface-level acceptance. Civil tolerance places a premium on the human experience and the defense of human rights while acknowledging the values inherent in all religious teachings. Muzadi’s four-dimensional concept of civil tolerance involves respecting diversity, acknowledging religious values, understanding human rights, and making collaborative efforts to build a more harmonious society. This research contributes to the discourse by presenting insights into how accepting such a nuanced form of tolerance can address existing problems as well as set the groundwork for a more inclusive society.